Could compression and traction loading improve the ability of magnetic resonance imaging to identify findings related to low back pain?. (December 2020) - Abdollah, Vahid; Parent, Eric C.; Su, Alex; Wachowicz, Keith; Battié, Michele C.
Abstract: Background: Diagnostic imaging is routinely used to depict structural abnormalities in people with low back pain (LBP), but most findings are prevalent in people with and without LBP. It has been suggested that LBP is related to changes induced in the spine due to loading. Therefore, new imaging measurements are needed to improve our ability to identify structures relating to LBP. Objectives: To investigate the response of the lumbar spine to compression and traction in participants with and without chronic LBP using MRI T2 -mapping. Method: Fifteen participants with chronic LBP were matched for age, weight, and gender with 15 healthy volunteers. All participants underwent MRI under three loading conditions maintained for 20 min each: resting supine, followed by compression and traction, both using 50% body weight. Participants were imaged in the last 5 min of each loading condition. Disc morphometric and fluid-based measurements from T2 -maps were obtained. Results: Traditional MRI measurements (i.e. disc height, width and mean signal intensity) were not able to capture any differences in the changes measured in response to loading between individuals with and without pain. The location of the T2 weighted centroid (WC) was able to capture the difference between groups in response to compression in the horizontal ( p < 0.01 ) and vertical direction ( p < 0.01 ), and in response to traction in the vertical direction ( p < 0.01 ). While the location of T2 WC moved anteriorly (Effect Size (ES): 0.44) and inferiorly with compression in those with pain (ES: 0.34), it moved posteriorly (ES: −0.14) and superiorly (ES: −0.05) in the group without pain. In response to traction, the vertical location of T2 WC moved superiorly in both groups but the change was larger in those with pain (ES Pain  = −0.52; ES No Pain : −0.13). Conclusion: The novel measurements of the location of the T2 WC in the intervertebral discs were the only measurements capturing differences in response to loading between those with and without low back pain. Graphical abstract: Image 1 Highlights: Loading may improve how MRI identifies structures related to low back pain (LBP). Participants with and without LBP matched for age, sex and weight were compared. Disc signal intensity and geometry responses did not differ between groups. New MRI features may help identify structures using MRI related to LBP. Location of the disc T2 -Weighted centroid differed in those with and without LBP.